Injustice as a Trigger of the Characters’ Significance Quest in Freaky Tales (2024) - Salsabiyla, Raddine; Wijaya, Kusuma; Pasopati, Rommel Utungga (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study explains how injustice becomes a trigger of the characters’ significance quest in the film Freaky Tales (2024). Using a qualitative method, this study helps the readers understand the context of the characters’ experiences and struggles in the film. Injustice in the film is presented through acts of oppression, intimidation, and unequal power that threaten the characters’ sense of safety and dignity. The analysis focuses on how the characters respond to injustice as a motivation to protect their identity, group, and personal meaning. These experiences of injustice encourage the characters to seek control, recognition, and a sense of significance. In conclusion, this study confirms that injustice plays an important role in shaping the characters’ actions and becomes a central trigger of their significance quest in Freaky Tales (2024).